Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

If [tex]\( p \)[/tex] is the hypothesis of a conditional statement and [tex]\( q \)[/tex] is the conclusion, which is represented by [tex]\( q \rightarrow p \)[/tex]?

A. the original conditional statement
B. the inverse of the original conditional statement
C. the converse of the original conditional statement
D. the contrapositive of the original conditional statement


Sagot :

To solve this problem, we need to understand the nature of different forms of conditional statements in logic. Let's start by defining these terms:

1. Original Conditional Statement: This is typically written as [tex]\( p \rightarrow q \)[/tex], where [tex]\( p \)[/tex] is the hypothesis and [tex]\( q \)[/tex] is the conclusion. It reads as "if [tex]\( p \)[/tex], then [tex]\( q \)[/tex]".

2. Converse: This statement reverses the hypothesis and the conclusion. The converse of [tex]\( p \rightarrow q \)[/tex] is [tex]\( q \rightarrow p \)[/tex]. It reads as "if [tex]\( q \)[/tex], then [tex]\( p \)[/tex]".

3. Inverse: This statement negates both the hypothesis and the conclusion of the original statement. The inverse of [tex]\( p \rightarrow q \)[/tex] is [tex]\( \neg p \rightarrow \neg q \)[/tex]. It reads as "if not [tex]\( p \)[/tex], then not [tex]\( q \)[/tex]".

4. Contrapositive: This statement both reverses and negates the original hypothesis and conclusion. The contrapositive of [tex]\( p \rightarrow q \)[/tex] is [tex]\( \neg q \rightarrow \neg p \)[/tex]. It reads as "if not [tex]\( q \)[/tex], then not [tex]\( p \)[/tex]".

Given the statement [tex]\( q \rightarrow p \)[/tex], we notice that the hypothesis ([tex]\( p \)[/tex]) and conclusion ([tex]\( q \)[/tex]) have been reversed compared to the original conditional statement [tex]\( p \rightarrow q \)[/tex].

Thus, [tex]\( q \rightarrow p \)[/tex] represents the converse of the original conditional statement [tex]\( p \rightarrow q \)[/tex].

Therefore, the correct answer is:
- The converse of the original conditional statement

So, [tex]\( q \rightarrow p \)[/tex] is the converse of the original conditional statement.